Physicochemical and in vitro antibacterial evaluation of metronidazole loaded eudragit S-100 nanofibrous mats for the intestinal drug delivery - Rade, Priyanka P.; Giram, Prabhanjan S.; Shitole, Ajinkya A.; Sharma, Neeti; Garnaik, Baijayantimala (Advanced Fiber Materials, 2021)
Metronidazole (MTZ) loaded Eudragit S-100 (ES-100) nonwoven nanofibrous mats were successfully electrospun and evaluated for intestinal drug delivery. MTZ was varied in the range of 1–15% (w/w) in ES-100 nanofibrous mats, the morphological characterization of nanofibrous mats was carried out using FE-SEM and the average diameter of nanofiber was found in the range 150–600 nm. WAXD and DSC demonstrated the amorphous nature of MTZ in ES-100 nanofibrous mats. Their contact angle analysis confirmed the hydrophobic nature. The mechanical strength of ES-100 nanofibrous mats decreased with increasing MTZ concentration. The drug release profiles showed 74% MTZ release from ES-100d within 2 h at pH 6.8 which is the colonic environment. Antibacterial activities against gram-positive bacteria (Staphylococcus aureus) and gram-negative bacteria (Escherichia coli) showed that the ES-100 nanofibrous mats loaded with MTZ exhibited good activity.